Application of immersed MF (IMF) followed by reverse osmosis (RO) membrane for wastewater reclamation: A case study in Malaysia. - Ujang, Zaini; Ng, K. S.; Tg. Hamzah, Tg. Hazmin; Roger, P.; Ismail, M. R.; Shahabudin, S. M.; Abdul Hamid, Mohd Harith (IWA Publishing, 2007)
A pilot scale membrane plant was constructed and monitored in Shah Alam, Malaysia for municipal wastewater reclamation for industrial application purposes. The aim of this study was to verify its suitability under the local conditions and environmental constraints for secondary wastewater reclamation. Immersed-type crossflow microfiltration (IMF) was selected as the pretreatment step before reverse osmosis filtration. Secondary wastewater after chlorine contact tank was selected as feed water. The results indicated that the membrane system is capable of producing a filtrate meeting the requirements of both WHO drinking water standards and Malaysian Effluent Standard A. With the application of an automatic backwash process, IMF performed well in hydraulic performance with low fouling rate being achieved. The investigations showed also that chemical cleaning is still needed because of some irreversible fouling by microorganisms always remains. RO treatment with IMF pretreatment process was significantly applicable for wastewater reuse purposes and promised good hydraulic performance.